Kehidupan Sosial Pedagang di Tepian Sungai Siak Bawah Jembatan Siak III Kota Pekanbaru - Resdati .; Yusmar Yusuf; Risdayati .; Mardatillah .; Amelia Idriana; Mutiara Mulyadi; ⁠Reyani Serlis; ⁠Ira Misra Ira Pratiwi; ⁠Sirah AlFatih (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The social life of traders along the Siak River waterfront beneath the Siak III Bridge in Pekanbaru City reflects the close relationship between economic activities and social interactions within the community. This study aims to describe the social life of traders formed through their daily interactions in the area. The research employed a qualitative method with a descriptive approach. Informants were selected purposively and consisted of traders and visitors. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the social life of traders is characterized by intensive communication, mutual cooperation, strong social solidarity, and healthy business competition. Relationships among traders and between traders and visitors are not merely based on economic interests but have developed into harmonious and family-like ties. The study concludes that the Siak River waterfront functions not only as an economic space but also as a social space that strengthens interaction, solidarity, and togetherness within the traders' community.